Morfogeneza slepe doline Brdanska dana - Kozamernik, Erika (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2016)
Brdanska dana blind valley is situated in the southwestern part of Slovenia where the flysch area of Brkini meets the limestone area of Matarsko podolje. The research area has features of fluvial and karstic geomorphic system, which is shown by a huge variety of geomorphological forms and processes. The morphogenetic interpretation of the geomorphological features, function and the evolution of the blind valley is discussed on the basis of data obtained through detailed geomorphological analysis.
Keywords: Brkini; Brkini Hills; doline; geomorfologija; geomorphology; kras (geologija); Matarsko podolje; relief; Slovenia; Slovenija; topography